A Geographical Perspective Of The Orchid Industry In West Malaysia - Ng, Gan Che (Universiti Sains Maslaysia, 1974)
Commercial orchid growing on a large scale is a recent phenomenon in Malaysia. The emergence of this industry, which has elevated the country to be the world’s third largest exporter of orchids, has been largely due to the diffusion of this idea from Singapore.